Necrosis by sodium overload-associated genes TRPM4 and SLC9A1: biological roles and clinical implications in breast cancer progression - Zhu, Yingze; Guo, Yaxin; Su, Yanlin; Zhang, Zhuoqi; Lu, Yige; Zhang, Xianghan; Pang, Hui (Frontiers in Immunology, 2025)
BackgroundBreast cancer persists as a principal contributor to global cancer mortality, driven by heterogeneous molecular pathways. Necrosis by sodium overload, a recently characterized form of regulated cell death, remains underexplored in oncogenesis. This study investigates the pathobiological significance and therapeutic potential of NECSO-related genes in breast cancer, elucidating their mechanistic roles in tumor progression.MethodsMulti-omics analyses were performed using transcriptomic data from TCGA and GEO cohorts (n = 1, 217), we systematically evaluated seven NECSO-related genes. Advanced bioinformatics pipelines included differential expression analysis, immune subtype profiling, functional state correlation, protein interaction mapping, and survival analytics. Experimental validation involved immunohistochemical evaluation of clinical samples.ResultsThrough multi-omics analysis of GEO and TCGA cohorts, we identified two sodium homeostasis-related genes, TRPM4 and SLC9A1, as consistently upregulated oncogenes in breast cancer, with significant diagnostic and prognostic relevance. Functional in vitro assays demonstrated that knockdown of either gene not only suppressed proliferation, colony formation, migration, and induced apoptosis in breast cancer cells, but also led to reduced expression of the sodium-calcium exchanger NCX1.ConclusionTRPM4 and SLC9A1 is a novel prognostic biomarker and potential therapeutic target in breast cancer. Dysregulated sodium homeostasis mediated by NECSO-related genes represents a targetable vulnerability in precision oncology.